Speroff's clinical gynecologic endocrinology and infertility - Taylor, Hugh S.; Pal, Lubna; Seli, Emre (Wolters Kluwer, 2020)
One of the world's most widely read gynecology texts for nearly 50 years, Speroff 's Clinical Gynecologic Endocrinology and Infertility provides a complete explanation of the female endocrine system and offers practical guidance for evaluation and treatment of common disorders. In this fully revised ninth edition, the editorial and author team from Yale School of Medicine have assumed the reins of Dr. Speroff's landmark work, retaining the clear, concise writing style and illustrations that clarify and explain complex concepts. This classic text remains indispensable for students, residents, and clinicians working in reproductive endocrinology and infertility, bringing readers up to date with recent advances that have occurred in this fast-changing field. Remains the definitive text on reproductive endocrinology, offering authoritative coverage of reproductive physiology, clinical endocrinology, contraception, and infertility. Contains two new chapters on transgender medicine and fertility preservation. Features many full-color illustrations, algorithms, and tables throughout. Retains Dr. Speroff's clear, user-friendly writing style while ensuring content is up to date with today's best clinical practices.